The Potential for Physiological Performance Curves to Shape Environmental Effects on Social Behavior - Killen, Shaun S.; Cortese, Daphne; Cotgrove, Lucy; Jolles, Jolle W.; Munson, Amelia; Ioannou, Christos C. (Frontiers in Physiology, 2021)
As individual animals are exposed to varying environmental conditions, phenotypic plasticity will occur in a vast array of physiological traits. For example, shifts in factors such as temperature and oxygen availability can affect the energy demand, cardiovascular system, and neuromuscular function of animals that in turn impact individual behaviour. Here, we argue that non-linear changes in the physiological traits and performance of animals across environmental gradients - known as physiological performance curves - may have wide-ranging effects on the behaviour of individual social group members and the functioning of animal social groups as a whole. Previous work has demonstrated how variation between individuals can have profound implications for socially living animals, as well as how environmental conditions affect social behaviour. However, the importance of variation between individuals in how they respond to environmental conditions has so far been largely overlooked in the context of animal social behaviour. First, we consider the broad effects that individual variation in performance curves may have on the behaviour of socially living animals, including changes in the rank order of performance capacity among group mates across environments, environment-dependent changes in the amount of among- and within-individual variation, and differences among group members in terms of the environmental optima, the critical environmental limits, and the peak capacity and breath of performance. We then consider the ecological implications of these effects for a range of socially mediated phenomena, including social foraging, within-group conflict, collective movement, within- and among group assortment, disease and parasite transfer, and predator-prey interactions. We end by outlining the empirical work required to test the implications for physiological performance curves in social behaviour.